Low Pain Tolerance Is Associated With Coronary Angiography, Coronary Artery Disease, and Mortality: The Tromsø Study - Kristina Fladseth (Wiley, 2021)
Background The initial presentation to coronary angiography and extent of coronary artery disease (CAD) vary greatly among patients, from ischemia with no obstructive CAD to myocardial infarction with 3‐vessel disease. Pain tolerance has been suggested as a potential mechanism for the variation in presentation of CAD. We aimed to investigate the association between pain tolerance, coronary angiography, CAD, and death. Methods and Results We identified 9576 participants in the Tromsø Study (2007–2008) who completed the cold‐pressor pain test, and had no prior history of CAD. The median follow‐up time was 10.4 years. We applied Cox‐regression models with age as time‐scale to calculate hazard ratios (HR). More women than men aborted the cold pressor test (39% versus 23%). Participants with low pain tolerance had 19% increased risk of coronary angiography (HR, 1.19 [95% CI, 1.03–1.38]) and 22% increased risk of obstructive CAD (HR, 1.22 [95% CI, 1.01–1.47]) adjusted by age as time‐scale and sex. Among women who underwent coronary angiography, low pain tolerance was associated with 54% increased risk of obstructive CAD (HR, 1.54 [95% CI, 1.09–2.18]) compared with high pain tolerance. There was no association between pain tolerance and nonobstructive CAD or clinical presentation to coronary angiography (ie, stable angina, unstable angina, and myocardial infarction). Participants with low pain tolerance had increased risk of mortality after adjustment for CAD and cardiovascular risk factors (HR, 1.40 [95% CI, 1.19–1.64]). Conclusions Low cold pressor pain tolerance is associated with a higher risk of coronary angiography and death.